Socioeconomic Inequality and Social Exclusion in Health: A Review - Chitra Bahadur Budhthoki (Dhaulagiri Journal of Sociology and Anthropology, 2013)
This paper examines the impact of social inequality and social exclusion on health. Social exclusion in health can be explained by socioeconomic inequality in health as socioeconomic position mediates access to resources including health services. Moreover, the impact of socioeconomic position on health is mediated by people's differential exposures to a very broad range of physical, chemical, biological, social, psychological and behavioral risk factors to health. People belong to upper strata of society in developed and developing countries have been experiencing higher level of life expectancy and better health status than those who are at the bottom of the society. There is evidence that societies that are more economically equal and socially cohesive have lower overall mortality than those that are more unequal. Interventions focusing on improving socioeconomic condition and increasing social inclusion and equity in social, economic and political dimensions can contribute to reduce inequities and social exclusion in health. DOI: http://dx.doi.org/10.3126/dsaj.v6i0.8477 Dhaulagiri Journal of Sociology and Anthropology Vol. 6, 2012 25-48